Analisis Upaya Peningkatan Kinerja Melalui Pemberian Sanksi Disiplin Pada Petugas Satpol PP Kota Bekasi - Dhea Perdana Coenraad (Majalah Bisnis & IPTEK, 2019)
This research is motivated by the large number of PP municipal police officers in Bekasi City who have not performed their duties properly and in accordance with applicable regulations including many officers who do not heed discipline which results in violations of the norms of the applicable rules so that the impact on the performance of the officers concerned . in this study the authors want to see the extent of the effectiveness of sanctions given to performance improvements that occur in Bekasi City Satpol PP Officers. The method that the authors do is a quantitative research method with different test analysis. The conclusion that I get is that giving disciplinary sanctions to officers who commit disciplinary violations will improve the performance of officers.